Мовні знаки чорнобильської доби у повісті Л. Даєна "Чорнобиль – трава гірка" - Гоцинець, І. (Культура слова, 2019)
У статті на матеріалі документальної повісті Леоніда Даєна «Чорнобиль – трава гірка» із погляду формування специфічно «чорнобильського» словника, підпорядкованого вербалізації актуальної для українського соціуму теми аварії на Чорнобильській АЕС, простежено стилістичну актуалізацію й змістово-оцінну динаміку мовних знаків чорнобильської доби. Висвітлено механізми образно-експресивного розвитку власної назви Чорнобиль. Відзначено типи змістово-оцінної трансформації традиційних образів, які потрапляють у поле семантичної дії номінації Чорнобиль. Об’єктами аналізу стали часово й тематично маркована лексика і фразеологія, а також стилістичні прийоми опису аварії на ЧАЕС. Зокрема, акцентовано на особливостях контекстуального освоєння одиниць термінологічного характеру – зона, атом, радіація, радіаційний тощо. З’ясовано особливості їхнього семантико- оцінного переосмислення при входженні в художньо-документальний текст. Наголошено на послідовній публіцистичній риториці мовоопису чорнобильських подій, особливо мовного портретування людей – ліквідаторів наслідків аварії на ЧАЕС. In the article on the material of L. Daien’s documentary story “Chornobyl is a bitter grass” the actualization and dynamics of language signs of the Chornobyl era in the context of the development of a specific “Chornobyl” dictionary is traced. This is in line with the needs of the verbalization of the topic of the technogenic accident at the Chornobyl nuclear power station, relevant to Ukrainian society. The mechanisms of the expressive development of Chornobyl’s own name are highlighted. The types of substantive-evaluative transformation of traditional images that fall into the semantic action of the Chornobyl nomination are noted. The objects of analysis were temporally and thematically marked vocabulary and phraseology, as well as stylistic methods of creating the image of the Chornobyl disaster. In particular, it emphasizes the peculiarities of contextual development of terminological units – zone, atom, radiation, radiation, etc. The types of their semantic-evaluative transformation as they enter the documentary text are clarified. The journalistic rhetoric of the linguistic description of the Chornobyl events, especially the linguistic portrayal of the liquidators of the consequences of the Chоrnobyl accident, was emphasized. Thus, the language of L. Daien’s documentary story “Chornobyl is a bitter grass” illustrates the social and psychological situation at the Chornobyl nuclear power station on the night of a man-made disaster. The verbalization of this topic is subordinated to the specific Chоrnobyl vocabulary, which reflects the entry into the common practice of narrowly specialized terms (atom, atomic, radiation, radioactive), and also attests to the expansion of the semantic volume of units, “involved”. Understood in the context of contemporary reading of documentary prose, they are perceived as linguistic signs of the Chоrnobyl era.